Pengaruh Konvergensi IFRS terhadap Manajemen Laba dengan Kepemilikan Institusional sebagai Variabel Moderasi (Studi empiris pada perusahaan pertambangan go public di BEI Periode 2009-2014) - I Made Laut Mertha Jaya (EBBANK, 2017)
This study aims to: (1) Determine the influence of convergence of IFRS on earnings management and (2) Determine the influence of institutional ownership in moderating the relationship between earnings management and IFRS convergence. The research method uses quantitative methods to conduct simple and multiple regression towards IFRS convergence variables, Institutional Ownership and Earnings Management. The study concluded that the IFRS convergence variable (x) a positive effect on earnings management and by applying a moderating variable in multiple linear regression analysis concludes that institutional ownership variable (z) as a moderating variable weak influence on the relationship between the convergence of IFRS (x) with earnings management (y). IFRS Convergence (x) a negative effect on earnings management (y) with a weak moderating influence of institutional ownership variable (z).